Bitter taste receptor agonists induce vasorelaxation in porcine coronary arteries - Ching-Chung Tsai; Ching-Chung Tsai; Yi-Chen Li; Li-Ching Chang; Shih-Che Huang (Frontiers in Pharmacology, 2025)
BackgroundIschemic heart disease (IHD) remains a leading cause of global morbidity and mortality, necessitating the search for novel therapeutic approaches. Recent studies have identified bitter taste receptors (TAS2Rs) in vascular smooth muscle cells as potential therapeutic targets because of their vasorelaxant properties. This study investigated the vasorelaxant effects of TAS2R agonists on porcine coronary arteries ex vivo and explored their potential as novel therapeutic targets for IHD.MethodsIsolated porcine coronary artery rings were precontracted using U46619 and treated with TAS2R agonists, including flufenamic acid, dapsone, phenanthroline, chloroquine, and quinine. Vasorelaxation induced by TAS2R agonists was quantitatively assessed, and pharmacological inhibitors were used to elucidate the underlying mechanisms of vasorelaxation. Real-time PCR analysis was conducted to confirm the expression of specific TAS2R subtypes in porcine coronary arterial tissue.ResultsTAS2R agonists induced concentration-dependent vasorelaxation, with flufenamic acid showing potent effects, exhibiting an EC50 of 30.4 μM, whereas phenanthroline and chloroquine exhibited moderate responses. In contrast, quinine and dapsone showed mild relaxation. The flufenamic acid-induced effect was attenuated by NG-nitro-L-arginine (47.4% ± 3.04%), apamin (49.2% ± 3.7%), and glibenclamide (49.6% ± 1.5%), indicating the involvement of nitric oxide signaling and potassium channels. PCR analysis revealed the differential expression of TAS2R subtypes, with TAS2R42 showing the highest expression, followed by subtypes 40, 10, and 38.ConclusionThis study showed that TAS2R agonists, especially flufenamic acid, phenanthroline, and chloroquine, induced vasorelaxation in isolated porcine coronary arteries. The vasorelaxation mechanism of flufenamic acid may involve nitric oxide signaling and potassium channels. The expression of specific TAS2R subtypes, together with functional observations, suggest that bitter taste receptors play a role in coronary vascular regulation, warranting further investigation into their therapeutic potential.